Relation between Periodontitis and Prediabetic Condition - Maboudi, Avideh (J Dent (Shiraz), 2019)
STATEMENT OF THE PROBLEM: Prediabetic condition, which is characterized by impaired glucose tolerance, impaired fasting blood glucose, and hemoglobin A1c (HbA1c) higher than normal might be associated with periodontitis. Early diagnosis of this condition might decrease consequent tissue damage caused by periodontitis. PURPOSE: The present study aimed to evaluate the association between prediabetes and periodontitis. MATERIALS AND METHOD: This cross-sectional study was conducted on 108 prediabetic patients screened by primary fasting blood sugar (FBS) test (100-125 mg/dL). Three subsequent blood tests including FBS, HbA1C, and oral glucose tolerance test (GTT) were performed for ultimate diagnosis of these patients. The periodontal health was evaluated by employing bleeding on probing (BOP), clinical attachment loss (CAL), and plaque index (PI), Lِe-Silness gingival index (GI), and pocket depth (PD). Data were analyzed by SPSS version 16, using t-test, ANOVA, and chi-square tests. RESULTS: The sample included 20 (19%) male and 88 (81%) female individuals with mean age of 49 years and mean BMI of 27.5. The mean FBS, GTT, and HbA1C were 107 MG/DL, 137MG/DL, and 5.9%, respectively. Clinical evaluation showed 33% of patients involved with periodontitis. The mean CAL, BOP, PI, PD, GI was 3.7, 0.62, 1.9, 2.1, 1.5, respectively (p< 0.05). A significant difference in periodontal index was found among patients with prediabetes. Moreover, in the patients with periodontitis, a statistically significant relationship between FBS and BMI, BOP and GTT, and finally between CAL and HbA1C was detected. CONCLUSION: Periodontitis is associated with prediabetic condition. While diabetes is an important risk factor for periodontitis, the risk of periodontitis would be greater if glycemic control is poor. Glycemic control in prediabetic patients can reduce the severity of periodontal disease. Early diagnosis and prevention is crucial to avoid the largely irreversible tissue damage that occurs in periodontitis.